Penggunaan Media Sosial Bagi Kecerdasan Milenial Pada Siswa Ma Al-Furqon - Ridwan Mustopa; Azi Azhari; Febri Noptageri (Universitas Garut, 2022)
Abstract The millennial generation is a generation born between the 1980s and the present. This generation is very familiar with the world of digital-based technology. The use of gadgets is part of their lifestyle. The instant use of technology has facilitated the various activities of this millennial generation. the use of media, especially social media among the millennial generation, is often the concern and spotlight of various groups, ranging from the executive, legislative, judiciary, as well as a number of elements of society such as teachers, lecturers, education observers and of course parents are not left behind. This study uses a qualitative descriptive research method with data sources using primary and secondary data and the data collection technique used is a questionnaire or a list of questions distributed online via the Google form. The purpose of this service is to describe the use of social media among adolescents, especially in social media. After distributing the online questionnaire via Google form and holding a digital literacy seminar with the theme of millennial intelligence on social media, it is expected that participants can use social media optimally. The results of this service show that Ma Al Furqon's students are not proficient enough in using social media. There are still some students who are not experts in using social media, but when compared, more are experts. They still use social media, especially gadgets according to their own pleasure, not according to their needs, as seen from the results of the percentage of using social media to find material for the benefit of academics is less than to look for other things on the internet. Keywords: Intelligence; social media; millennials; MA Al-Furqan. Abstrak Generasi milenial adalah sebuah generasi yang lahir antara tahun 1980an sampai sekarang. Generasi ini amat akrab dengan dunia teknologi berbasis digital. Penggunaan gadget merupakan bahagian dari lifestyle mereka. Pemanfaatan teknologi yang instan telah memudahkan beragam aktivitas generasi milenial ini. penggunaan media, khsusunya media sosial dikalangan generasi milenial sering menjadi perhatian dan sorotan dari beragam kalangan mulai dari kalangan eksekutif, legislatif, yudikatif, juga sejumlah elemen masyarakat seperti para guru, dosen, pemerhati pendidikan dan tentunya tidak ketinggalan para orang tua. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dengan sumber data menggunakan data primer dan sekunder serta teknik pengumpulan data yang digunakan adalah kuesioner atau daftar pertanyaan yang disebar secara online melalui google form. Tujuan pengabdian ini untuk mendeskripsikan penggunaan media sosial di kalangan remaja khususnya dalam bermedia sosial. Setelah disebarkannya kuesioner online melalui google form dan dilaksanakannya seminar literasi digital dengan tema kecerdasan milenial bermedia sosial diharapkan peserta dapat menggunakan media sosial dengan optimal. Hasil pengabdian ini menunjukkan bahwa siswa Ma Al Furqon belum cukup cakap dalam menggunakan media sosial. Masih terdapat beberapa siswa yang belum ahli dalam menggunakan media sosial tetapi jika di bandingkan lebih banyak yang sudah ahli. Mereka masih menggunakan media sosial khususnya gedget sesuai dengan kesenangan mereka bukan sesuai kebutuhan, seperti dilihat dari hasil presentase penggunaan media sosial untuk mencari materi untuk kepentingan akademisi lebih sedikit dibanding untuk mencari hal-hal lain di internet.Kata-kata kunci: Kecerdasan; media social; milenial; MA Al-Furqon.